2014
DOI: 10.1371/journal.pntd.0002712
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Proteinuria in Adult Dengue Severity

Abstract: BackgroundDengue is an important viral infection with different presentations. Predicting disease severity is important in triaging patients requiring hospital care. We aim to study the value of proteinuria in predicting the development of dengue hemorrhagic fever (DHF), utility of urine dipstick test as a rapid prognostic tool.Methodology and principal findingsAdult patients with undifferentiated fever (n = 293) were prospectively enrolled at the Infectious Disease Research Clinic at Tan Tock Seng Hospital, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
3
13
1
4
Order By: Relevance
“…In a study by Vasanwala et al concluded that urine protein creatinine ratio done at onset and around the time before fever subsided predicted the likelihood of developing dengue hemorrhagic fever. 9 In a report by Mendez et al it was shown that the incidence of proteinuria in dengue was 62% which was comparable to our study.…”
Section: Discussionsupporting
confidence: 92%
“…In a study by Vasanwala et al concluded that urine protein creatinine ratio done at onset and around the time before fever subsided predicted the likelihood of developing dengue hemorrhagic fever. 9 In a report by Mendez et al it was shown that the incidence of proteinuria in dengue was 62% which was comparable to our study.…”
Section: Discussionsupporting
confidence: 92%
“…(Bethell et al, 2001; Vasanwala et al, 2014; Wills et al, 2004) This is consistent with the elevated extracellular water observed during defervescence in patients with DHF in comparison to patients with DF(Libraty et al, 2002b) Increased urinary excretion of small protein molecules such as albumin and transferrin was elevated during shock phase in severe dengue cases in comparison to the excretion rate measured after recovery(Vasanwala et al, 2014; Wills et al, 2004) In addition, increased heparin sulfate urinary excretion was also observed. Although glomerular vascular bed is not the major site where leakage occurs in DHF, these findings may reflect the perturbation of vascular permeability regulation that occurs at other anatomical sites such as the pleural and abdominal cavities.…”
Section: Dengue Virus and The Endothelial Barriersupporting
confidence: 77%
“…La hipoalbuminemia y proteinuria son bien reconocidos en la infección por dengue. Esto se cree se debe a la alteración de la filtración alterada por alteración del glicocálix, como el virus del dengue y NS1 son conocidos por unirse a sulfato de heparán, que es parte de la glicocálix [27][28] . La infección por dengue ha sido asociada con una variedad de desórdenes renales: injuria renal aguda, proteinuria, hematuria y glomerulonefritis han sido reportadas durante o poco tiempo después de la infección 29 .…”
Section: Dengue Y Afectación Renalunclassified
“…Los pacientes con dengue leve tuvieron proteinuria significativamente más bajos que los pacientes con dengue hemorrágico inminente y choque por dengue. El seguimiento diario en este estudio prospectivo permitió determinar el valor discriminatorio de proteinuria, que no fue evidente en el período febril temprano pero sí entre los días 4 y 7, justo antes de desaparición de la fiebre y coincidente con la fuga plasmática 27 . Se llegaría así a la conclusión de que la aparición y el pico de proteinuria mediante una prueba UPCR basada en el laboratorio se asocia significativamente con el desarrollo posterior de dengue hemorrágico, ya sea en ambulatorios u hospitalizados.…”
Section: Falla Renal Agudaunclassified
See 1 more Smart Citation